الاتزان الانفعالي وعلاقته بالتفكير السريع – البطي وتعلم مهارة التهديف السلمي بكرة السلة - نهاد محمد علوان; هبة فاضل حسين (الرياضة المعاصرة)
Balancing is the control of the distribution of human energy, whether it is emotional, physical or mental, and the problem of research is that the game of basketball is one of the games that need to be linked with physical abilities in addition to thinking. The Lay up shot consists of several steps, and the player cannot perform it without having thinking, as well as an emotional balance to control the performance of the steps of Lay up shot. Therefore, the researcher conducted this research to find the relationship between emotional balance and fast- slow thinking and skill of Lay up shot in basketball to reach the best solution for good performance. The research aims to identify: 1- The relationship between the emotional balance and the fast – slow thinking. 2- The relationship between the emotional balance and the skill of Lay up shot in basketball. To achieve these objectives, the researcher used the descriptive approach and selected a sample of (28) students in which the scale of emotional equilibrium was applied and the scale of fast- slow thinking and the test of Lay up shot in basketball skill. After collecting the data and treating them statistically by using laws (Pearson correlation coefficient - multiple correlation coefficient) to verify the validity of the study hypotheses, It was reached the following results: 1- Emotional balance is directly proportional to quick-slow thinking, whenever student's balancing increases, her thinking ability also increases and thus increased her ability to learn skills. 2-Emotional balance works on improving the player's level well, leading to of learn layup shot better